Parenthood and Adolescence mental health. Differences by Geographic Location and school belonging - Casassus Rodino, Martín; Valdés Correa, Macarena; Florenzano Urzúa, Ramón; Cáceres Contreras, Eugenio; Aspillaga Herrera, Carolina; Santander Rigollet, Sylvia (Revista de Psicología, 2011)
Parenting styles influence adolescent´s mental health. Previous work has corroborated the explicative model proposed by Brian Barber that correlates parental variables (psychological control, behavioral control, social support) with adolescent functional behaviors (depression, antisocial behavior, social initiative). In this study the model is applied in a representative sample of students in three Chilean cities with different administrative school systems. Results: the model fits in the overall sample, but presents differences by city and school system. Social initiative doesn’t correlate with parental support in Antofagasta, but it does in Santiago and Concepción. Depressions indexes are higher in private schools; state subsidized schools present the lower scores in the antisocial behavior scale.